2018
DOI: 10.1002/ps.5171
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive overexpression of cytochrome P450 monooxygenase genes contributes to chlorantraniliprole resistance in Chilo suppressalis (Walker)

Abstract: Multiple overexpressed P450 genes were potentially associated with chlorantraniliprole resistance, as confirmed by the RNA interference (RNAi) assay. Our findings suggested that metabolic resistance to chlorantraniliprole might be mediated by P450s. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
33
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 28 publications
(43 reference statements)
7
33
1
Order By: Relevance
“…A previous resistance monitoring study showed that C. suppressalis in the Jiangxi, Hunan, Henan, and Zhejiang provinces of China developed moderate to high resistance to chlorantraniliprole (64.10- to 249.60-fold) in the field [1,2,8]. In the present study, we found that C. suppressalis could develop high-level resistance to chlorantraniliprole in the laboratory under selection pressure, which was in line with previous findings [8,9]. The results indicated that C. suppressalis populations from different geographical areas seem to have a remarkable ability to develop resistance to this insecticide under continuous pressure.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…A previous resistance monitoring study showed that C. suppressalis in the Jiangxi, Hunan, Henan, and Zhejiang provinces of China developed moderate to high resistance to chlorantraniliprole (64.10- to 249.60-fold) in the field [1,2,8]. In the present study, we found that C. suppressalis could develop high-level resistance to chlorantraniliprole in the laboratory under selection pressure, which was in line with previous findings [8,9]. The results indicated that C. suppressalis populations from different geographical areas seem to have a remarkable ability to develop resistance to this insecticide under continuous pressure.…”
Section: Discussionsupporting
confidence: 92%
“…To confirm a functional role of the overexpressed UGT genes in chlorantraniliprole resistance, we performed gene-silencing RNAi assays. Such technology has previously been used to analyze gene functions in C. suppressalis and has shown potential for developing new pest control measures [9,16,29]. Our results showed that dsRNA injection significantly silenced the target genes.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations